2014
DOI: 10.1007/jhep09(2014)170
|View full text |Cite
|
Sign up to set email alerts
|

Non-geometric orbifolds and wrapping rules

Abstract: Abstract:We show that the number of half-supersymmetric p-branes in the Type II theories compactified on orbifolds is determined by the wrapping rules recently introduced, provided that one accounts correctly for both geometric and non-geometric T-dual configurations. Starting from the Type II theories compactified on K3, we analyze their toroidal dimensional reductions, showing how the resulting half-supersymmetric p-branes satisfy the wrapping rules only by taking into account all the possible higher-dimensi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…This prediction is based on the analysis of roots and weights of the U-duality group at any dimension [25][26][27][28][29][30]. Lately, the so-called wrapping rules were formulated [11,17,[31][32][33]. This set of rules allows one to construct a set of mixed-symmetry potentials, depending on the type of T -and S-duality transformations that one performs.…”
Section: 1 Backgroundmentioning
confidence: 99%
“…This prediction is based on the analysis of roots and weights of the U-duality group at any dimension [25][26][27][28][29][30]. Lately, the so-called wrapping rules were formulated [11,17,[31][32][33]. This set of rules allows one to construct a set of mixed-symmetry potentials, depending on the type of T -and S-duality transformations that one performs.…”
Section: 1 Backgroundmentioning
confidence: 99%
“…3 Wrapping rules for IIA/IIB on (T 4 /Z 2 ) × T n In [27,28] it was shown that the wrapping rules satisfied by the branes of the maximal theory are still valid if one compactifies the Type IIA and Type IIB string theories to the six dimensional N = (1, 1) and N = (2, 0) theories on the orbifold T 4 /Z 2 , provided that only even cycles are taken into account. In [26] it was then shown that if the six-dimensional theory is further reduced on a torus, the resulting branes with α = 0, −1, −2, −3 are obtained starting from the six-dimensional ones by applying the standard wrapping rules. The aim of this section is to first review how the branes of the six-dimensional theories result from applying the wrapping rules of the maximal theory with only even cycles taken…”
Section: Wrapping Rules For Iia/iib On T Nmentioning
confidence: 99%
“…into account, and then move to the lower-dimensional case showing that the analysis of [26] can be extended so that all the branes of the (T 4 /Z 2 ) × T n theory result from generalised wrapping rules, where as explained in the previous section additional multiplicity factors given by the mixed-symmetry indices of the potentials involved have to be taken into account.…”
Section: Wrapping Rules For Iia/iib On T Nmentioning
confidence: 99%
See 1 more Smart Citation
“…In a series of papers, the full classification of 1/2-BPS branes in type-II string theory compactified on a torus was achieved by analysing the supersymmetry of the corresponding brane effective action [39][40][41]44], while the connection of this analysis with specific group theory properties of such branes was shown in [42,43]. This classification was also extended to theories with less supersymmetry in [64][65][66][67]. In the following, we will first review the basic results of this classification and we will then derive a universal T-duality transformation rule for any brane in string theory, which will give in particular the IIA branes that are related by duality to the S-dual of the D7-brane in our model, together with additional branes in IIB that must be included for consistency.…”
Section: T-duality Rules and Exotic Branesmentioning
confidence: 99%